Materialising careers: the role of artefacts in career making - Van den Abeele, Hannelore Ottilie (2020)
We know artists from their work. It is a common sense that artists and artworks they produce are the same or entangled and interchangeable. However, in career studies there is little mention of artefacts – i.e. objects made by people – in careers. This lack of attention is curious because in organisation studies for the past decade, there has been a lively interest in the role of materiality in social processes Carlile, Nicolini, Langley, and Tsoukas (2013). In this thesis, I want to apply these emerging ideas to artistic careers. A review of the literature of creative careers showed that career studies understand creative careers as sequences of steps and transitions organised around artefacts, whereby artefacts signal the skills, networks and identity of the producers (Jones, 1996, 2002; McLeod, O'Donohoe, & Townley, 2011). Creative careers are also understood as highly dependent on the networks or patterns of relationships, to which they are connected (Giuffre, 1999; Jones, 2010). Taking both approaches together, one can think about creative careers as evolving networks organised around artefacts. However, except for just one study (Jones, 2010), artefacts have previously appeared in career studies as passive or as resources for people. Specifically, Jones’ study demonstrated that buildings play a role in architects’ career development and in the various networks in which they operate. Inspired by that study I wanted to know what the role of artefacts is in career making. Can they be more than a signal for skills, networks and identity? Can we think of them as playing an active role in career making? The initial research question “what role do artefacts play in career making?” was informed by the literature and re-constructed into three research sub-questions: “how does an artefact act upon a career?”, “how does an artefact become and remain active”, and “what is the relationship between the artefact and its maker in the process of career making?” To answer these questions, the conventional methods in career research (surveys and interviews) are not satisfactory. Rather, we need a methodology that focuses on the temporal and spatial context in which artefacts move. I draw on Actor-Network-Theory (ANT) and conducted an ethnographic case study with a single artefact as unit of analysis. The setting was the field of contemporary arts. I shadowed the artwork No Life Lost I 2014-2015 (2015) (NLL I) of visual artist Berlinde De Bruyckere (BDB). The study relies on a data set that includes more than 250 hours of observations, 17 interviews, and archival resources which were recorded as field notes and pictures, transcripts and documents. The present study contributes to the knowledge of creative careers in several ways. First, the study challenges two main assumptions within careers literature: the prevailing notions that career action is restricted to people, and that career actors (such as networks, artefacts and the makers) and their relationships are stable. Instead, the study shows first that artefacts are career actors too and second that career actors and their relationships are fluid and multiple. Second, it refines our understanding of networks in career studies by adding symbolic and material networks to social networks. It does so by showing that the network in which NLL I is connected, includes ideas, artefacts, spaces, and materials as well and that each of them plays a different role. Symbolic networks such as names, texts, and artworks in situ tell how to understand the oeuvre and career, whereas material networks embody that understanding and enable longevity and travelling. Third, it deepens our knowledge of career making by including a process view on networks and artefacts. In particular, it details how and to what end networks, as well as artefacts, are formed and evolve, and how that evolution impacts the career and vice versa. Fourth, it extends our knowledge by presenting a new perspective for career studies: the “material career” or the oeuvre as materialised career. Fifth, it extends our way of studying careers by foregrounding and using a chronological perspective. The method of shadowing an artefact brought me in the heat of career action. It made me see the accomplishment of an artist’s career in real-time. The present study also contributes to career research methodologically and empirically. The thesis introduces ANT as an appropriate method for showing how artefacts act upon career processes. Empirically, it adds the setting of visual arts to creative career research, a domain within creative industries that received little attention to date (Oakley, 2009).